Language configurations of degree-related denotations in the spoken production of a group of colombian EFL university students: A corpus-based study - Escobar, Wilder Yesid (Colombian Applied Linguistics Journal, 2015)
Developing the competences needed to appropriately use linguistic resources according to contextual characteristics (pragmatics) is as important as the culturally-imbedded linguistic knowledge itself (semantics), and both are equally essential to form competent speakers of English in foreign language contexts. As such, this investigation relies on corpus linguistics to analyze both the scope and the limitations of the sociolinguistic knowledge and the communicative skills of English students at university level. To this end, a linguistic corpus was collected from spoken production of EFL learners, compared to an existing corpus of native speakers, and analyzed in terms of the frequency, overuse, underuse, misuse, ambiguity, success, and failure of the linguistic parameters used in speech acts. The findings herein describe the linguistic configurations employed to modify levels and degrees of descriptions (salient semantic theme exhibited in the EFL learners’ corpus). The study discovered problems regarding the students’ production in terms of wrong word choices or forms, faulty word combinations, and incomplete or unsystematic structuring of expressions. It concludes that expressions aiming at conveying or modifying degree are complex and should be viewed as units which require modeling for a better appropriation of an in-context understanding of its linguistic use which corpus can assist.